'********************************************************************
'* Solve Y' = F(X,Y) with Initial Condition Y(X0)=Y0 using the *
'* Adams-Bashforth Method *
'* ---------------------------------------------------------------- *
'* REFERENCE: "Méthode de calcul numérique- Tome 2 - Programmes en *
'* Basic et en Pascal By Claude Nowakowski, Edition du *
'* P.S.I., 1984" [4]. *
'* ---------------------------------------------------------------- *
'* SAMPLE RUN: *
'* (Solve Y' = -Y + X/((1+X)*(1+X)) with Y(0)=1 for X0=0 up to *
'* X1=1.0, exact solution is Y = 1 / (1+X). *
'* *
'* X Y Y exact Error *
'* ----------------------------------------------- *
'* 0.000000 1.000000 1.000000 0 *
'* 0.000000 1.000000 1.000000 0.000000 *
'* 0.050000 0.952381 0.952381 0.000000 *
'* 0.100000 0.909091 0.909091 0.000000 *
'* 0.150000 0.869525 0.869565 0.000040 *
'* 0.200000 0.833265 0.833333 0.000068 *
'* 0.250000 0.799910 0.800000 0.000090 *
'* 0.300000 0.769125 0.769231 0.000106 *
'* 0.350000 0.740623 0.740741 0.000117 *
'* 0.400000 0.714160 0.714286 0.000125 *
'* 0.450000 0.689525 0.689655 0.000131 *
'* 0.500000 0.666533 0.666667 0.000134 *
'* 0.550000 0.645026 0.645161 0.000135 *
'* 0.600000 0.624865 0.625000 0.000135 *
'* 0.650000 0.605926 0.606061 0.000134 *
'* 0.700000 0.588103 0.588235 0.000133 *
'* 0.750000 0.571298 0.571429 0.000131 *
'* 0.800000 0.555428 0.555556 0.000128 *
'* 0.850000 0.540416 0.540541 0.000125 *
'* 0.900000 0.526194 0.526316 0.000121 *
'* 0.950000 0.512703 0.512821 0.000118 *
'* 1.000000 0.499886 0.500000 0.000114 *
'* ----------------------------------------------- *
'* *
'* Basic Release By J-P Moreau, Paris. *
'* (www.jpmoreau.fr) *
'********************************************************************
DefDbl A-H, O-Z
DefInt I-N
Option Base 0
H = 0.05 'integration step
Dim B(4), X(4), Y(4)
'Initial conditions
X(0) = 0# 'starting X
X1 = 1# 'ending X
Y(0) = 1# 'initial Y
'write header
Cls
Print
Print " X Y Y exact Error "
Print " ------------------------------------------------"
'write initial line
F$ = "#####.######"
Print USING; F$; X(0);
Print USING; F$; Y(0);
Print USING; F$; Y(0);
Print " 0"
'use Runge-Kutta to start
For K = 0 To 1
GoSub 1000 'call RK4
XX = X(K + 1): GoSub 600: ER = Abs(FX - Y(K + 1))
Print USING; F$; X(K + 1);
Print USING; F$; Y(K + 1);
Print USING; F$; FX;
Print USING; F$; ER
Next K
'main integration loop
While X(2) < X1
For I = 1 To 3
XX = X(3 - I): YY = Y(3 - I): GoSub 500
B(I) = F
Next I
X(3) = X(2) + H
Y(3) = Y(2) + H * (23# * B(1) - 16# * B(2) + 5# * B(3)) / 12#
XX = X(3): GoSub 600: ER = Abs(Y(3) - FX)
Print USING; F$; X(3);
Print USING; F$; Y(3);
Print USING; F$; FX;
Print USING; F$; ER
For K = 0 To 2
X(K) = X(K + 1): Y(K) = Y(K + 1)
Next K
Wend
Print " ------------------------------------------------"
End
'User defined function Y'=F(XX,YY)
500 F = -YY + XX / ((1# + XX) * (1# + XX))
Return
'Exact solution Y=FX(XX)
600 FX = 1# / (1# + XX)
Return
'Runge-Kutta method to calculate first points only
1000 XX = X(K): YY = Y(K): GoSub 500: C1 = F
XX = X(K) + H / 2#: YY = Y(K) + H / 2# * C1: GoSub 500: C2 = F
XX = X(K) + H / 2#: YY = Y(K) + H / 2# * C2: GoSub 500: C3 = F
XX = X(K) + H: YY = Y(K) + H * C3: GoSub 500: C4 = F
X(K + 1) = X(K) + H
Y(K + 1) = Y(K) + H * (C1 + 2 * C2 + 2 * C3 + C4) / 6#
Return
'end of file adambash.bas
EXPLANATION FILE OF PROGRAM ADAMBASH
====================================
Ordinary Differential Equations Y' = F(x,y)
-------------------------------------------
Linked Steps Method
-------------------
We have seen that Euler, Runge-Kutta... methods can be put under the general
form:
y = y + h phi(x , y , h)
n+1 n n n
and each point y of the solution is only determined from previous point, y
n+1 n
Calculations are made for y1, y2,...,yn-1, yn, yn+1... These methods are cal-
led "with separate steps": each step is independant from the previous one. To
obtain a given accuracy, each step has to be divided into intermediate steps.
Let us take an example:
For the Runge-Kutta method of order 4, we use the formulas:
k1 = h f(xn, yn)
k2 = h f(xn+h/2, yn+k1/2)
k3 = h f(xn+h/2, yn+k2/2)
k4 = h f(xn+h, yn+k3)
y = y + (1/6)(k1+2k2+2k3+k4)
n+1 n
Another method consists in using the previous calculations to improve speed;
the y point is evaluated from y , y and y points.
n+1 n n-1 n-2
The general formula is:
y = a y + a y + ... + a y
n+1 0 n 1 n-1 k n-k
+ h (b f + b f + b f + ... + b f
-1 n+1 0 n 1 n-1 k n-k
This can be written as:
k k
y = Sum a y + h Sum b f
n+1 j=0 j n-j j=-1 j n-j
These methods are called "with linked steps" and f(x,y) evaluations are only
made at points x0, x1, x2,..., xn.
If b = 0, the process is explicit; y is directly obtained by applying the
-1 n+1
formula.
If b <> 0, the process is implicit: we must solve an equation of the form
-1
y = phi(y ) to obtain y .
n+1 n+1 n+1
For the three first points, y1, y2, y3, we have no previous points to calcu-
late them: these methods cannot start by themselves like "with separate steps"
methods.
The truncation error Tn is estimated by using the Taylor formula for y(x )
n+j
(jh)² (jh)^p (p)
y(x ) = y(x ) + jhy'(x ) + ----- y"(x ) + ... + ------ y (x )
n+j n n 2! n p! n
+ h^p eps(h)
and also for f(x , y(x )):
n+j n+j
f(x , y(x )) = y'(x +jh)
n+j n+j n p-1
h (jh) (p)
= y'(x ) + j y"(x ) + ... + -------- y (x ) + h^p eps(h)
n n (p-1)! n
Example: let us estimate the truncation error for the implicit formula:
y = y + (h/2) (f + f )
n+1 n n+1 n
T = y(x ) - y
n+1 n+1 n+1
3
y(x ) = y(x ) + hy'(x ) + (h^2/2) y"(x ) + (h^3/3) y"'(x ) + h eps(h)
n+1 n n n n
2 3
(h/2) f = (h/2) y'(x + h) = (h/2) y'(x ) + (h /2) y"(x ) + (h /4)
n+1 n n n
3
y"'(x ) + h eps(h)
n
(h/2) f = (h/2) y'(x )
n n
Hence y(x ) - y = y(x ) - y + (h/2) (f + f ) =
n+1 n+1 n+1 n n+1 n
3 3
= (h /12) y"'(x ) + h eps(h)
n
Here the method is of order two.
The methods with separate steps can be integrated by the formula
xn+2h
y(x ) - y(x ) = Sum f(t,y(t)) dt
n+1 n-M xn
and by applying the Simpson's formula
b b - a a + h
Sum (f(t) dt = ----- {f(x) + 4f(-----) + f(b)}
a 6 2
Hence y - y = (h/3)[f + 4f + f ]
n+2 n n n+1 n+2
Here we have an implicit process.
In a more general way, knowing y , y , y , we can calculate f , f ,
n n-1 n-2 n n-1
f and approximate y' = f(x,y) by an interpolation polynomial at points
n-2
x , x , x :
n n-1 n-2 x
n+1
y = y + Sum P(x) dx
n+1 n-M x
n-M
where y is an approximation of y(x ) and y is an approximation of
n-M n-M n+1
y(x ).
n+1
In the case of an implicit method, y(x ) can be approximated by the formula:
n+1
x
p n+1
y = y + Sum P(x) dx
n+1 n-M x
n-M
p p
This allows evaluating f = f(x , y ) and we can resume the interpolation
n+1 n+1 n+1
step with a new polynomial P*(x). y is calculated by the correction formula
n+1
x
c n+1
y = y + Sum P*(x) dx
n+1 n-M x
n-M
As the points are equally spaced and indices are decreasing, xn, xn-1, xn-2...
we can use the Newton formula with back diferences:
Div (f ) = f - f
n n n-1
2
Div (f ) = f - 2f +f
n n n-1 n-2
--------------------------
k |k| |k| k
Div (f ) = f - | | f | | f +...+ (-1) f
n n |1| n-1 |2| n-2 n-k
Hence x 2
p n+1 Div(fn) Div (fn)
y = y + Sum [f + ------- (x-x ) + -------- (x-x )(x-x ) + ...
n+1 n-M x n h n 2h^2 n n-1
n-M
k
Div (fn)
+ -------- (x-x )(x-x )...(x-x )] dx
k! h^k n n-1 n-k+1
Let us put u = (x-x )/h, then du = dx/dh and
n 2
p 1 Div (fn)
y = y + Sum [f + Div(f )u + -------- u(u+1) + ...
n+1 n-M -M n n 2
k
Div (fn)
+ -------- u(u+1)(u+2)...(u+k-1) h du
k!
After integration:
p _ _ _ 2 _ k
y = y + h [P f + P Div(f ) + P Div (f ) + ... + P Div (f )]
n+1 n-M 0 n 1 n 2 n k n
_ 1 1
where P = -- Sum u(u+1)(u+2)...(u+j-1) du
j j! -M
j |j| |j| j
and Div (f ) = f - | | f | | f +...+ (-1) f
n n |1| n-1 |2| n-2 n-j
|j| j!
with | | = --------- (Newton's coefficients)
|m| m! (j-m)!
Fianally p
y = y
n+1 n-M + h [P f + P f + ... + P f ]
0 n 1 n-1 k n-k
Example: M=3, k=2
x 2
p n+1 Div(fn) Div (fn)
y = y + Sum [f + ------- (x-x ) + -------- (x-x )(x-x )] dx
n+1 n-3 x n n n 2h² n n-1
n-3
Let us put u = (x-xn)/h, then
2
p 1 Div (fn)
y = y + Sum [f + Div(f ) u + -------- u (u+1)] h du
n+1 n-3 -3 n n 2
After integration:
p 2
y = y + h [4f - 4 Div(f ) + (8/3)Div (f )
n+1 n-3 n n n
This leads to the Milne's formula (explicit process):
p
y = y + (4h/3) [2f - f + 2f ]
n+1 n-3 n n-1 n-2
We do in a similar way for the implicit process. For example, with M=1 and
k=2, the Milne's corrector formula is:
c
y = y + (h/3) [f + 4f + f ]
n+1 n-1 n+1 n n-1
This corresponds to the numerical integration of
x
n+1
Sum f(x) dx by the Simpson's method.
x
n-1
For the Adams-Moulton's implicit formulas, we have:
p h
k=1 y = y + - [3f - f ]
n+1 n 2 n n-1
c h
y = y + - [f + f ]
n+1 n 2 n+1 n
p h
k=2 y = y + -- [23f - 16f + 5f ]
n+1 n 12 n n-1 n-2
c h
y = y + -- [5f + 8f - f ]
n+1 n 12 n+1 n n-1
p h
k=3 y = y + -- [55f - 59f + 17f - 9f ]
n+1 n 24 n n-1 n-2 n-3
c h
y = y + -- [9f + 19f - 5f +f ]
n+1 n 24 n+1 n n-1 n-2
p h
k=4 y = y + --- [1901f - 2984f + 2616f - 1274f + 251f ]
n+1 n 720 n n-1 n-2 n-3 n-4
c h
y = y + --- [251f + 646f - 264f +106f - 19f ]
n+1 n 720 n+1 n n-1 n-2 n-3
In these formulas, the main part of what is left aside in the integration
corresponds to the truncation error.
3
c h "'
Example: for y = y + (h/2) (f + f ) - -- y (ksi)
n+1 n n+1 n 12
with x <= ksi <= x
n n+1
Another way to obtain an explicit or implicit process is using a recursive
formula:
y = a y + a y + ... + a y
n+1 0 n 1 n-1 k n-k
+ h [b f + b f + ... + b y ]
-1 n+1 0 n k n-k
For y, the polynomial of greatest degree is:
y(x) = 1, y'(x) = 0
y(x) = x, y'(x) = 1
y(x) = x², y'(x) = 2x
---------------------
m m-1
y(x) = x , y'(x) = mx
So
1 = a0 + a1 + ... + ak
x = (x-h)a + (x-2h)a + ... + ha + b +b + b + ... +b
0 1 k-1 -1 0 1 k
x² = (x-h)²a + (x-2h)²a + ... + ha
0 1 k-1
+ 2 [xb +(x-h)b + ... + hb
-1 0 k-1
--------------------------------------------------
l l l
x = (x-h) a + (x-2h) a + ... + ha
0 1 k-1
l-1 l-1
+ l [x b +(x-h) b + ... + hb
-1 0 k-1
Example: Nystroem's explicit formula:
3
y = y + h Sum b f
n+1 n-1 j=0 j n-j
3 2
y = x , y' = 3x
3 3
==> y = x , y = (x-2h)
n+1 n-1
2 2 2
f = y' = 3(x-h) , f = 3(x-2h) , f = 3(x-3h)
n n n-1 n-2
3 2 2 2 2
==> x = (x-2h) + 3h [b (x-h) + b (x-2h) + b (x-3h)
0 1 2
By developing and identifying:
b0 + b1 + b2 = 2
b0 + 2b1 +3b2 = 2
b0 + 4b1 + 9b2 = 8/3
We find: b0 = 7, b1 = -2, b2 = 1.
So we have the Adams's formulas:
Explicit, order 2: y = y + h/2 (3f - f )
n+1 n n n-1
order 3: y = y + h/12 (23f - 16f + 5f )
n+1 n n n-1 n-2
Implicit, order 2: y = y + h/2 (f + f )
n+1 n n+1 n
and Nystroem's formulas:
Explicit, order 2: y = y + 2h f
n+1 n-1 n
order 3: y = y + h/3 (7f - 2f + f )
n+1 n+1 n n-1 n-2
Implicit, order 3: y = y + h/12 (f + 4f -f )
n+1 n-1 n+1 n n-1
From [BIBLI 04].
------------------------------------------------
End of file adambash.txt
pievemre_ko Keri Gali Download crack
ReplyDeleteelexnutga
narodiuneLowell Susan Ortega Here
ReplyDeletebapcompmondse
VsicalPac-me Shane Shepard download
ReplyDeleteclick
link
download
reahihobi
AcageMcir-po-Milwaukee Sandra Lee This is there
ReplyDeletethere
download now
maulennagold